Skeletal Muscle Lymphoma Presenting with Chronic Compartment Syndrome of Leg after Trauma - Jhong-You Li; Chung-Liang Li; Chun-Kuan Lu (Case Reports in Oncological Medicine)
Compartment syndrome may be acute or chronic based on the clinical course and etiology. Here, we report the first known case to be diagnosed with skeletal muscle-derived B-cell lymphoma presenting with chronic compartment syndrome after trauma. A 62-year-old woman sought medical attention due to a one-month history of painful left lower leg swelling and paresthesia of the medial side of the foot after falling over. The patient underwent fasciotomy and debridement under the preoperative diagnosis of fasciitis and myositis with associated compressive neuropathy. Preoperative laboratory tests were within normal limits. Postoperative pathologic examination and bone marrow aspiration revealed B-cell lymphoma with bone marrow involvement postoperatively. Tumor lysis syndrome took place, presenting with drowsiness, poor appetite, and oliguria, after the operation along with multiple organ failure. Awareness of the differential diagnoses of compartment syndrome in such clinical situation is crucial because it may lead to different examination and treatment plan preoperatively.